Getting Ready to Move as a Couple: Accomplishing Mobile Formations in a Dance Class. (May 2014) - Broth, Mathias; Keevallik, Leelo
The article focuses on how students in a Lindy Hop dance class move into a complex mobile formation as a sequentially relevant response to a directive embedded in the teachers' verbal and embodied instructions of the next task for practice. This sequence of actions accomplishes a transition from a stationary constellation of observing students to a mobile circle of practicing dance couples. The article describes in detail how instruction is turned into practice in an emergent way, in and through the simultaneous accountable production and reception of qualitative instruction, practice proposals, structuring instructions, and count-ins . The analysis shows how student behavior is oriented to the couple as a relevant mobile formation and how couples gradually become more synchronized with each other.